2020
DOI: 10.1016/j.atmosres.2019.104656
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of biogenic VOC emissions and their corresponding impact on ozone and secondary organic aerosol formation in China

Abstract: Biogenic volatile organic compounds (BVOC) play an important role in global environmental chemistry and climate. In the present work, biogenic emissions from China in 2017 were estimated based on the Model of Emissions of Gases and Aerosols from Nature (MEGAN). The effects of BVOC emissions on ozone and secondary organic aerosol (SOA) formation were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(60 citation statements)
references
References 60 publications
7
53
0
Order By: Relevance
“…According to the studies of Su et al (2017), Zheng et al (2019) and Wu et al (2019), it can be deduced that NO x has been significantly reduced by about 60%, at least 2 times the reduction of VOCs in Hangzhou. The influence of stringent emission control measures on VOCs is not as immediate an effect as that on NO x , which is associated with the fact that there was a large amount of biogenic VOC emission in Hangzhou and surrounding regions (Liu et al, 2018;Wu et al, 2020). In fact, the average temperature during the study period is as high as around 31 • C (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to the studies of Su et al (2017), Zheng et al (2019) and Wu et al (2019), it can be deduced that NO x has been significantly reduced by about 60%, at least 2 times the reduction of VOCs in Hangzhou. The influence of stringent emission control measures on VOCs is not as immediate an effect as that on NO x , which is associated with the fact that there was a large amount of biogenic VOC emission in Hangzhou and surrounding regions (Liu et al, 2018;Wu et al, 2020). In fact, the average temperature during the study period is as high as around 31 • C (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Hangzhou, the capital of Zhejiang Province, is located in the center of the Yangtze River Delta, which is one of the most developed areas in China. Resulting from local emissions (Wu et al, 2014;Hu et al, 2015) and transboundary transport of aerosol and trace gases (Liu et al, 2015;Ni et al, 2018;Zhang et al, 2018), air pollution in Hangzhou has become serious in recent years. In 2016, Hangzhou hosted the G20 (Group of 20 Finance Ministers and Central Bank Governors) summit from 4 to 6 September.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, most of the SOC formation is due to the ozone induced oxidation of monoterpenes like α-pinene, β-pinene and limonene ( Watne et al, 2017 ). Recently Wu et al (2020) have shown that 70% of SOC is formed from the BVOCs in China.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Biogenic volatile organic compounds (BVOCs) emitted by plants are important in emission and air pollution research, as they are significant contributors of secondary air pollutants, including ozone and secondary fine particles [20][21][22].…”
Section: Biogenic Emissions: the Megan Modelmentioning
confidence: 99%